Keanekaragaman dan Parasitisasi Parasitoid Telur Leptocorisa Acuta pada Berbagai Pola Tanam Padi - AISAH JAMILI; HERY HARYANTO (Fakultas Pertanian Universitas Udayana, 2014)
Diversity and parasitization of egg parasitoid of Leptocorisa acuta on various rice cropping pattern. Study on parasitoid diversity and their parasitization on various rice cropping pattern was conducted during April - October 2012. Exploration of egg parasitoids was conducted by collecting host eggs from rice field in Lombok Island. Sample of Insect were collected by hand. Two species have been identified, namely Ooencyrtus malayensis and Hadronotus leptocorisae. The result showed that eggs of both parasitoid were distributed in all locations with composition 50%. Generally, three times rice cropping pattern showed higher rate of parasitization (31,45%) compared to two times (22,69%) and once cropping pattern (18,03%). Parasitoid and diversity index were similar in different time, although the tend to increase linearly with the rice growth. The Shannon diversity index H’ between 0,24-0,30. Domination index 0,62-0,51, evenness index (E) 0,35-0,43. The result suggest that parasitoid diversity and parasitization is depend on many factors, including rice cropping pattern.